การเปิดรับข้อมูลข่าวสารอาเซียน การรับรู้ และทัศนคติต่ออัตลักษณ์อาเซียน ที่มีผลต่อการปรับตัวของประชาชนในกรุงเทพมหานคร - ภักดีบุรุษ(Worawudh Phakdiburut) วรวุฒิ (Journal of Behavioral Science for Development, 2016)
(ASEAN Information Exposure, Perception and Attitude towards ASEAN Identity affecting the Adjustment among People in Bangkok) Abstract The research aimed to investigate 1) the level of ASEAN information exposure, perception of ASEAN identity , attitude towards ASEAN identity and adjustment to ASEAN identity among people in Bangkok 2) the correlation between ASEAN information exposure and perception of ASEAN identity , and ASEAN information exposure and attitude towards ASEAN identity among people in Bangkok 3) ASEAN information exposure, perception and attitude towards ASEAN identity affecting the adjustment among people in Bangkok. Samples were the total of 400 people in Bangkok who were selected by multi- stage random sampling technique. Data were collected using a questionnaire with the reliability of .93, .88, .94 , and .96 respectively. Statistical data analysis used descriptive statistic, Pearson product moment correlation coefficients and multiple regression analysis. The research findings were as follows: 1) ASEAN information exposure among people in Bangkok was at the high level. Their perception of ASEAN identity, attitude towards ASEAN identity and adjustment to ASEAN identity were at the moderate level. 2) ASEAN information exposure among people in Bangkok was not correlated to perception of ASEAN identity, ASEAN information exposure was positively correlated to attitude towards ASEAN identity with statistical significance at 0.01 3) ASEAN information exposure, perception of ASEAN identity, attitude towards ASEAN identity could predict the adjustment among people in Bangkok to ASEAN identity with 51.90 percentage. The important predictor was an attitude towards ASEAN identity. Keywords: ASEAN Information Exposure, Perception, Attitude, Adjustment,ASEAN Identity